1999
DOI: 10.1029/1998ja900037
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated ISTP satellite and ground observations of morningside Pc5 waves

Abstract: Abstract. This paper reports the result of a coordinated data analysis of a morningside Pc5 event observed at different altitudes in the magnetosphere and also on the ground. The event took place during 1400-1500 UT of April 29, 1993. The Geotail satellite was located in the boundary region and observed a 5-min quasi-periodic magnetic oscillation. The oscillation was mostly transverse to the background magnetic field. A 90 ø phase lag between the magnetic field and electric field variations was not clear, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 62 publications
5
14
0
Order By: Relevance
“…Station B15 recorded two different frequencies during Event 6, one of which was within 0.1 mHz of the two Cluster dominating frequencies. Events 1, 5, and 6 were similar to the previously published results obtained by Ohtani et al (1999) whom discovered dominating frequencies within 0.2 mHz of the spacecraft frequency. All oscillation frequencies were higher in the ground magnetometer data than the Cluster data.…”
Section: Supermag Signaturessupporting
confidence: 89%
See 4 more Smart Citations
“…Station B15 recorded two different frequencies during Event 6, one of which was within 0.1 mHz of the two Cluster dominating frequencies. Events 1, 5, and 6 were similar to the previously published results obtained by Ohtani et al (1999) whom discovered dominating frequencies within 0.2 mHz of the spacecraft frequency. All oscillation frequencies were higher in the ground magnetometer data than the Cluster data.…”
Section: Supermag Signaturessupporting
confidence: 89%
“…These magnetic latitudes were less than the latitudes at which Lui (1989) and Farrugia et al (1994) observed their auroral bright spots and where McHenry et al (1990) observed traveling convection vortices. The mapped magnetic latitude range was similar to where Ohtani et al (1999) observed the Pc5 magnetometer pulsations.…”
Section: Conclusion and Discussionsupporting
confidence: 75%
See 3 more Smart Citations